2020
DOI: 10.1038/s41420-020-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of noncoding RNAs in epithelial cancer

Abstract: Regulatory noncoding RNAs (ncRNAs) are a class of RNAs transcribed by regions of the human genome that do not encode for proteins. The three main members of this class, named microRNA, long noncoding RNA, and circular RNA play a key role in the regulation of gene expression, eventually shaping critical cellular processes. Compelling experimental evidence shows that ncRNAs function either as tumor suppressors or oncogenes by participating in the regulation of one or several cancer hallmarks, including evading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 150 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…lncRNAs have received increasing attention in the past decade due to their important roles in human cancer types ( 32 , 33 ). Numerous lncRNAs, such as ubiquitin conjugating enzyme E2 R2-AS1 ( 34 ), colorectal neoplasia differentially expressed ( 35 ) and snail family transcriptional repressor 3-AS1 ( 36 ), are differentially expressed in HCC and are closely associated with clinicopathological factors and prognosis of patients with HCC ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have received increasing attention in the past decade due to their important roles in human cancer types ( 32 , 33 ). Numerous lncRNAs, such as ubiquitin conjugating enzyme E2 R2-AS1 ( 34 ), colorectal neoplasia differentially expressed ( 35 ) and snail family transcriptional repressor 3-AS1 ( 36 ), are differentially expressed in HCC and are closely associated with clinicopathological factors and prognosis of patients with HCC ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, lncRNAs have received considerable attention because of their important roles in human cancers. [40][41][42] An increasing number of studies have reported that several lncRNAs are differentially expressed in CRC and contribute to colorectal carcinogenesis and cancer. [43][44][45] LncRNAs promote or suppress diverse malignant processes in CRC, playing oncogenic or tumor-suppressing roles.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study revealed that oncomiR genes were favorably located in amplified regions, in contrast to tumor-suppressive miRNA genes that tended to be localized to deleted regions. Similar studies have allowed researchers to identify hundreds of novel miRNAs in many cancer types [ 81 , 82 , 83 , 84 ]. Further, it is well established that in order for primary tumor cells to metastasize to distant organs, tumor cells must interact with the surrounding microenvironment.…”
Section: Roles Of Exosomal Micrornas In Breast Cancer Metastasismentioning
confidence: 99%